2022
DOI: 10.1037/cfp0000240
|View full text |Cite
|
Sign up to set email alerts
|

Couples’ division of household responsibilities during COVID-19, perceptions of fairness, and relationship functioning.

Abstract: As couples adapted to the stressful, pandemic-induced disruptions to daily life (e.g., closures of schools, working from home), many couples experienced changes to established divisions of paid and household labor. The present study investigates whether contributions to household responsibilities and perceptions of fairness in divisions of labor are associated with couple relationship satisfaction and disagreements. Gender, number of children in a family, and financial stress during the pandemic are included a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 42 publications
3
10
0
Order By: Relevance
“…Thus, greater life satisfaction was reported by mothers who had co‐responsible partners and who felt satisfied with the distribution of housework, the amount of free time available to them and the childcare resources to which they had access. This is consistent with both our initial hypothesis and that reported in the extant literature (Ciciolla & Luthar, 2019; Ryjova et al, 2022; Tornello, 2020; Tornello et al, 2015). Conversely, those who perceived to have more problems related to work‐life balance also had lower levels of life satisfaction, in line with what has been found to date (Haar et al, 2014; Riva et al, 2019).…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…Thus, greater life satisfaction was reported by mothers who had co‐responsible partners and who felt satisfied with the distribution of housework, the amount of free time available to them and the childcare resources to which they had access. This is consistent with both our initial hypothesis and that reported in the extant literature (Ciciolla & Luthar, 2019; Ryjova et al, 2022; Tornello, 2020; Tornello et al, 2015). Conversely, those who perceived to have more problems related to work‐life balance also had lower levels of life satisfaction, in line with what has been found to date (Haar et al, 2014; Riva et al, 2019).…”
Section: Discussionsupporting
confidence: 94%
“…Given the results outlined above, it is hardly surprising that certain differences were also observed in the whole sample in terms of life satisfaction. The mothers with same-sex partners in our study reported a higher level of life satisfaction than those with different-sex partners, which is consistent with their higher level of satisfaction with the distribution of housework and childcare, a relationship repeatedly found in the scientific literature (Ciciolla & Luthar, 2019;Ryjova et al, 2022;Tornello, 2020;Tornello et al, 2015). It is also not surprising that the Swedish mothers in our study reported higher levels of life satisfaction than their Spanish counterparts.…”
Section: Sociocultural Context and Distribution Of Housework And Chil...supporting
confidence: 90%
See 3 more Smart Citations